CFD Analysis for a New Trombe Wall Concept - Alexandru-Mihai BULMEZ; Alin-Ionuț BREZEANU; George DRAGOMIR; Mariana FRATU; Nicolae Fani IORDAN; Sorin Ionuț BOLOCAN; Lucian ROZOREA; Eugen Călin POPA; Gabriel NĂSTASE (MDPI; Buildings, 2024)
The envelope (façade) of a building is the first barrier between the exterior and the interior of the building and withstands the highest variation in temperature and solar radiation. Trombe walls are used to take advantage of that and contribute to the heating of interior air, helping the heating system. In this study, a new Trombe wall design is presented to contribute significantly to the indoor ventilation of residential buildings. For this, an exterior wall equipped with a proposed Trombe system was studied in a numerical simulation analysis. The proposed systems consist of two important sections, an exterior one and an interior one. The air cavities on the exterior of the wall, covered with silica glass, are the first heat-transfer layer. The secondary layer used for heat transfer, on the interior, is comprised of a MPCLB wall of 115 mm. The air circulation from the exterior to the interior was established as forced convection with a ventilator. The air circulates through the first heating layer on the exterior air cavities and then passes through the second heating layer on the interior MPCLBs. Two cities in Romania were considered to represent the coldest and hoAest climates in Romania. Brașov represents the cold climate and Constanța represents the hot climate. In the investigation, both the presence and absence of solar radiation were taken into account. In total, four cases were established. For all four cases, monthly research was made using monthly mean temperatures, and direct and diffuse solar radiation. The results are promising and illustrate that the system works best during the transitional seasons of spring and autumn. The lower the outdoor temperature, the higher the temperature can be increased. Overall, solar radiation accounted for an average 2 °C increase. The temperature increase varied between 3.4 °C and 15.99 °C for Brașov and between 6.42 °C and 12.07 °C in Constanța. This study presents an alternative way to use the Trombe wall for indoor ventilation purposes throughout the year, compared to traditional uses for the Trombe wall for indoor heating.